Secure transactions using mobile agents with TTP - Han, Song; Chang, Elizabeth; Dillon, Tharam S. (IEEE, 2005)
Electronic commerce has pushed and benefited from the development of mobile agents technology. One of the reasons is electronic commerce needs remote searching and negotiating between one customer and a number of E-shops. Mobile agents can travel over the Intranet or Internet. Therefore, mobile agents can help the customer or E-shops with remote searching and negotiating. However, because of the heterogeneousness of the networks the mobile agents migrate to, security issues should be tackled with cautions. This paper presents a new secure electronic commerce protocol. The underlying transactions are accomplished with mobile agents. A trusted third party (in fact, a trusted authority) is involved in the protocol.